Grid interaction and environmental impact of a net zero energy building. (1st January 2020) - Tumminia, G.; Guarino, F.; Longo, S.; Aloisio, D.; Cellura, S.; Sergi, F.; Brunaccini, G.; Antonucci, V.; Ferraro, M.
Graphical abstract: Highlights: A novel design methodology for NZEBs design. A coherent framework for the implementation of NZEBs into the existent power grids. Use of batteries at building scale largely decreases the reliance on power grid. SOFC fed by natural gas allows a good load match at high energy efficiency. Abstract: The concept of Net Zero Energy Building (NZEB), as a grid-connected building that generates as much energy as it uses over a given period, has been developing through policies and research agendas during the last decade as a contribution towards the decarbonization of the building sector. However, since the most applicable and widely used renewable energy supply options are non-programmable, the large-scale NZEBs diffusion into the existing power grids can seriously affect their stability having a relapse on operation costs and environmental impacts. In this context, the study aims at performing the design of the energy systems to be used in the case-study through a wide numbers of point of views, including the grid interaction, global warming potential, and different design alternatives such as using fuel cells and renewable energy generation systems and drawing lessons learned to be saved for similar buildings. A novel approach for developing for NZEBs, combining load match and grid interaction indicators with an environmental impact indicator, is proposed. The proposed design approach allows for the quantification of the power grid interaction and environmental impact (in terms of Global Warming Potential) aiming to find trade-offs between the opposing tendencies of building energy performances and the need to limit the embodied carbon within building envelope and systems. The design approach has been used to investigate the performances of a NZEB prototype with the aim to explore the effectiveness of the solution sets used in the current design (only Photovoltaic system) and plan different solutions (batteries and fuel cells system) for the future ones. For the base case, even though the overall PV energy generation (8069 kWhe ) in a year surpasses the electricity consumption (5290 kWhe ), on a yearly base only the 29% of the PV generation is used on-site. Hence, the assessed indicators show clearly how installing a PV system merely able to cover the energy uses on a yearly net base (or even slightly oversized) will have stress implications on the power grid. On the other hand, the use of batteries at the building scale largely decreases the reliance on power grid when not programmable renewable sources are present. Moreover, if coupled to the right size of the on-site generation systems, the storage system could increases the environmental benefits arising from the renewable energy technologies (the GHG emission reaches its minimum value of 0.92·10 3 kg CO2eq /year, with a reduction of the 50.4% if compared to the base case) for a storage capacity of 20 kWh and a PV system nominal power of 4.56 kW). Fuel cells guarantee a good load match at high energy efficiency, furthermore, a high installed power of fuel cells is not required to obtain high load cover factor values. On the other hand, since the specific CO2eq emission per unit of energy of the fuel cells are high, the CO2eq emissions are always greater than those of the base case if the system is equipped with a fuel cell system. Therefore, future research will have to focus on the eco-design of fuel cells with to reduce environmental impacts of these systems in a life cycle perspective.